Analytical sociology and social mechanisms - Demeulenaere, Pierre (Cambridge University Press, 2011)
"Mechanisms are very much a part of social life. For example, we can see that inequality has tended to increase over time and that cities can become segregated. But how do such mechanisms work? Analytical sociology is an influential approach to sociology which holds that explanations of social phenomena should focus on the social mechanisms that bring them about. This book evaluates the major features of this approach, focusing on the significance of the notion of mechanism. Leading scholars seek to answer a number of questions in order to explore all the relevant dimensions of mechanism-based explanations in social sciences. How do social mechanisms link together individual actions and social environments? What is the role of multi-agent modelling in the conceptualization of mechanisms? Does the notion of mechanism solve the problem of relevance in social sciences explanations?"--